8.9 Microstructural Changes in Neonatal Encephalopathy Revealed with the Neurite Orientation Dispersion and Density Imaging (NODDI) Model. (9th June 2014) - Lally, PJ; Zhang, H; Pauliah, SS; Price, DL; Bainbridge, A; Balraj, G; Cady, EB; Shankaran, S; Thayyil, S
Abstract : Background: Although diffusion tensor imaging (DTI) fractional anisotropy (FA) is commonly used to quantify neural injury, it is non-specific and affected by a number of microstructural changes. Objective: To examine alterations in white matter (WM) associated with neonatal encephalopathy (NE), and relate these to tangible biophysical changes using the neurite orientation dispersion and density imaging (NODDI) model. Design/Methods: We recruited with parental consent consecutive encephalopathic neonates (Thompson score ≥6) admitted to Calicut Medical College, India over a 6 month period. At age <3 wk diffusion tensor magnetic resonance imaging (DTI, TR/TE = 2800 ms/94 ms, 20 directions, b = 0&1000 s/mm 2, 1.8 × 1.8 × 5 mm 3 ) was performed at 1.5T (Siemens Avanto). Sarnat encephalopathy stage (none, mild, moderate or severe) was allocated at day 3. DTI data were fitted to the NODDI model, generating maps of orientation dispersion index (ODI) and neurite density index (NDI). These were compared between infants grouped by encephalopathy severity using tract-based spatial statistics (TBSS). Results: Fifty-four infants were recruited; 31 had usable data. The mean FA skeleton is shown in green (Figure 1a ). Compared to normal/mild (n = 22) the moderate/severe encephalopathy group (n = 9) had significantly reduced WM FA (Figure 1b : red p < 0.05; yellow p < 0.01) and increased radial diffusivity (RD, Figure 1c ). This corresponded to a decrease in NDI (Figure 1d ), but not ODI (Figure 1e ). Conclusions: In this cohort, NODDI fitting indicates that microstructural changes in NE may be due to a reduced neurite density. Further work will establish whether these findings are consistent with those obtained from gold-standard multi-shell diffusion data.